(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: To develop the preparation process and quality assessment of the “NGL” powdered extract which originates from the “Nhat gan linh” traditional medicine. Subjects and methods: Preparation of “NGL” powdered extract (including 15 medicinal materials: Radix Glehniae, Radix Rehmanniae glutinosae, Radix Angelicae sinensis, Fructus Meliae toosendan, Polyporus, Poria, Rhizoma Alismatis, Styli et stigmata Maydis, Cortex Phellodendri, Cortex Radicis Paeoniae suffruticosae, Fructus Corni officinalis, Fructus aurantii immaturus, Radix Bupleuri chinensis, Radix Eurycomae longifoliae, Radix Paeoniae lactiflorae) via hot extraction combined and spray-drying technique. The quality assessment of powdered extract included morphology, density index, compression index, loss on drying. Results: Liquid extract NGL 3:1 was prepared using extract solvent as water, material; solvent 1:6 g/mL, extraction temperature 700C, extraction time 60 minutes, repeated 2 times. The spray-drying parameters were determined: mixure of spray-drying excipients maltodextrin:aerosil (30:70 w/w), excipients: extract solid 3:7 w/w; percentage of solid in spray solvent 15%, spray-drying temperature 1400C, speed of feed 30 ml/min; pump pressure 0.2 Mpa. The spray-drying yield was 91.80%; recovery yield of saikosaponin A and berberin was 92.54% and 86.38%, respectively. The quality parameters of NGL powdered extract included: dried and separated powder, loss on drying less than 5%; CI 32.82 ± 0,21%; content of saikosaponin A and berberin were 5.27 ± 0.02 and 93.33 ± 0.03 (mg/g), respectively. Conclusions: The preparation process of the “NGL” powder was established using the spray-drying technique. The spray-drying parameters in preparation process of the “NGL” powder were also investigated. The powder quality was tested. This study contributed to a scientific base for further in-depth studies in order to prepare other dosage forms.